Una propuesta transmedia para educadores: Nodus Project (2020)
The project presents a dialogue between digital humanities and pedagogy. This convergence would provide a didactic alternative for the teaching of humanities through new narratives and spaces that today can be asset in the educational process outside the classroom. The objective is to involve teachers as active actors in the design of a proposal that integrates academic purposes and new forms of content presentation through a transmedia experience, which expands the subject in various platforms outside of the traditional classroom's tools. In this sense, the project recognizes the concept of Personal Learning Environments (EPA), as expanded learning elements using narratives, content found in social networks and other tipical elements in entretaiment. Finally, the process is approached from the Participatory Design method, which allows the intervention of the public in the design of a digital experience route. In this case, the method was developed through a transmedia narrative that includes multiple platforms and tools (video, podcast, photography, among others).